Pelatihan Pembuatan Sabun Mandi Ekstrak Minyak Sereh sebagai Sabun Anti Nyamuk bagi Ibu PKK Kecamatan Ciracas Jakarta Timur - Liszulfah Roza; Mega Elvianasti; Mirza Nur Hidayat (Universitas Mathla'ul Anwar Banten, 2020)
TRAINING FOR MAKING SOAP FROM LEMONGRASS EXTRACT AS ANTI MOSQUITO SOAP FOR PKK WOMEN IN CIRACAS DISTRICT, EAST JAKARTA. The implementation of community service activities by providing soap and body scrub training is a meaningful business for mothers. Transparent soap and anti-mosquito body scrub which is one of the home industry products can be a capital for mothers to foster their creativity and foster an entrepreneurial spirit for them. This training aims to provide knowledge about making soap and body scrubs some simple technologies that can be applied easily and do not require special skills. Even though it is a simple activity, but this activity in the process still requires knowledge of the natural ingredients used. The materials used in the soap and body scrub process are very easy to find in the surrounding environment. Community service in general covers three activities, namely the participant's data collection, the delivery of material by the tentor namely lecturers, and the assistance of the practice of making soap by students. This training activity lasted a day and was attended by 35 PKK members. The practice of making soap and body scrubs runs smoothly and each group is given soap and body scrubs that have been made previously by the speaker to be tested on the benefits at home by each participant. A few days after the use of soap and especially body scrubs, three trainees reported the benefits they felt were loss of aches, flatulence and colds which he felt after using natural body scrubs with hill salt and lemongrass ingredients before bathing.